The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10549-017-4340-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of first and subsequent recurrence in women with early breast cancer

Abstract: PurposeLittle is known about the occurrence, timing and prognostic factors for first and also subsequent local (LR), regional (RR) or distant (DM) breast cancer recurrence. As current follow-up is still consensus-based, more information on the patterns and predictors of subsequent recurrences can inform more personalized follow-up decisions.MethodsWomen diagnosed with stage I-III invasive breast cancer who were treated with curative intent were selected from the Netherlands Cancer Registry (N = 9342). Extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
57
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 40 publications
(43 reference statements)
9
57
2
Order By: Relevance
“…This suggests not only that for the latter two subtypes rates are lower in the Netherlands, but also that luminal A and B may have a greater tendency to recur later on in the follow‐up. This highlights the importance of at least 10 years of follow‐up when studying recurrences, as demonstrated in several studies . The same Canadian study showed that distant metastases occurred in 6.4% of luminal A, 12.1% of luminal B, 19.2% of HER2 positive and 27.4% of triple negative breast cancers, while in our study these percentages were 9.5, 20.0, 25.6 and 23.2%.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This suggests not only that for the latter two subtypes rates are lower in the Netherlands, but also that luminal A and B may have a greater tendency to recur later on in the follow‐up. This highlights the importance of at least 10 years of follow‐up when studying recurrences, as demonstrated in several studies . The same Canadian study showed that distant metastases occurred in 6.4% of luminal A, 12.1% of luminal B, 19.2% of HER2 positive and 27.4% of triple negative breast cancers, while in our study these percentages were 9.5, 20.0, 25.6 and 23.2%.…”
Section: Discussionsupporting
confidence: 73%
“…Another Chinese study with a median follow‐up of 5.7 years demonstrated local recurrences rates of 12.7, 15.7, 19.1 and 20.9% in luminal A, luminal B, HER2 positive and triple negative subtypes, respectively, which is very high compared to our results. Interestingly, a preceding Dutch study showed that the hazard of recurrences was highest around 2 years after diagnosis, and that a second (smaller) peak was observed around 9 years after diagnosis . In our study, the peak at 9 years was less pronounced, but mostly visible for distant metastasis in the luminal A and luminal B subtype, which may possibly be related to an extinguished effect of endocrine therapy .…”
Section: Discussionsupporting
confidence: 43%
“…This study is constrained by being a single institution, retrospective study, and patients may have been treated or diagnosed with the recurrence elsewhere. However, this study is unique in its patient cohort, as it compared only unicentric disease enabling salvage lumpectomy in both salvage lumpectomy and mastectomy groups, with over 60% of the patients in both groups undergoing breast MRI prior to surgical decision …”
Section: Discussionmentioning
confidence: 99%
“…And as almost half of those second recurrences are detected in the first year after the previous recurrence and more than 80% are DM, more intensive follow-up for early detection subsequent recurrence is not likely to be (cost-)effective. 29 In summary, we demonstrated how follow-up could be personalized based on the risk of recurrence for different age categories using a POMDP. With optimal risk-based follow-up schedules, clinicians will be able to make informed decisions and focus resources on patients with higher risk, while avoiding unnecessary and potentially harmful follow-up visits for women with very low risks.…”
Section: Discussionmentioning
confidence: 87%
“…Sending them back into the model will provide unreliable estimates. Geurts et al found that although the risk of subsequent recurrence is high after the first recurrence, the absolute incidence remains low. And as almost half of those second recurrences are detected in the first year after the previous recurrence and more than 80% are DM, more intensive follow‐up for early detection subsequent recurrence is not likely to be (cost‐)effective …”
Section: Discussionmentioning
confidence: 99%